2022
DOI: 10.1177/09544100221088362
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and optimization of a radiating fin array

Abstract: Space radiators are used to reject waste heat from power units, electronic devices, and various equipment in space vehicles. It is important that radiators can achieve the heat desired to be dissipated into space with the least mass. With a view to ensuring this aim, the heat transfer calculations that must be performed must be highly accurate. Therefore, the variation of conductivity with temperature should also be taken into account in the mathematical model. This paper presents heat transfer performance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Fins play a crucial role in thermal management by acting as extended surfaces that facilitate the transfer of excess heat from the primary surface, such as equipment, to the surrounding environment. This transfer mechanism is necessary to maintain the desired operating temperature of the primary surface 1 . The effectiveness of the rows lies in their ability to increase the available surface for heat exchange with the adjacent refrigerant, which increases the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Fins play a crucial role in thermal management by acting as extended surfaces that facilitate the transfer of excess heat from the primary surface, such as equipment, to the surrounding environment. This transfer mechanism is necessary to maintain the desired operating temperature of the primary surface 1 . The effectiveness of the rows lies in their ability to increase the available surface for heat exchange with the adjacent refrigerant, which increases the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Arslanturk 2 reported that the maximum heat transfer rate per unit mass from the heat pipe radiator with step fins is higher than the plain fins. The radiative coupling between the radiator fin surface and fin base, along with the variation of thermal conductivity with temperature, are incorporated by Arslanturk 3 and Solak 4 to increase the accuracy of heat transfer rate estimation from the radiator. Wang and Peterson 5 optimized the micro heat pipe radiators wherein two thin sheets are embedded with an array of metal wires.…”
Section: Introductionmentioning
confidence: 99%